Heterogeneities in the Ecoepidemiology of Trypanosoma cruzi Infection in Rural Communities of the Argentinean Chaco - Cardinal, Marta Victoria (2014)
We conducted a cross-sectional survey of Trypanosoma cruzi infection of Triatoma infestans as well as dogs and cats in 327 households from a well-defined rural area in northeastern Argentina to test whether the household distribution of infection differed between local ethnic groups (Tobas and Creoles) and identify risk factors for host infection. Overall prevalence of infection of bugs (27.2%; 95% confidence interval = 25.3–29.3%), dogs (26.0%; 95% confidence interval = 23.3–30.1%), and cats examined (28.7%; 95% confidence interval = 20.2–39.0%) was similar. A multimodel inference approach showed that infection in dogs was associated strongly with the intensity and duration of local exposure to infected bugs and moderately with household ethnic background. Overall, Toba households were at a substantially greater risk of infection than Creole households. The strong heterogeneities in the distribution of bug, dog, and cat infections at household, village, and ethnic group levels may be used for targeted vector and disease control.